Cow Milk Extracellular Vesicle Effects on an In Vitro Model of Intestinal Inflammation - Samanta Mecocci; Alessio Ottaviani; Elisabetta Razzuoli; Paola Fiorani; Daniele Pietrucci; Chiara Grazia De Ciucis; Silvia Dei Giudici; Giulia Franzoni; Giovanni Chillemi; Katia Cappelli (Biomedicines, 2022)
Extracellular vesicles (EVs) are lipid bilayer nano-dimensional spherical structures and act mainly as signaling mediators between cells, in particular modulating immunity and inflammation. Milk-derived EVs (mEVs) can have immunomodulatory and anti-inflammatory effects, and milk is one of the most promising food sources of EVs. In this context, this study aimed to evaluate bovine mEVs anti-inflammatory and immunomodulating effects on an in vitro co-culture (Caco-2 and THP-1) model of intestinal inflammation through gene expression evaluation with RT-qPCR and cytokine release through ELISA. After establishing a pro-inflammatory environment due to IFN-γ and LPS stimuli, CXCL8, IL1B, TNFA, IL12A, IL23A, TGFB1, NOS2, and MMP9 were significantly up-regulated in inflamed Caco-2 compared to the basal co-culture. Moreover, IL-17, IL-1β, IL-6, TNF-α release was increased in supernatants of THP-1. The mEV administration partially restored initial conditions with an effective anti-inflammatory activity. Indeed, a decrease in gene expression and protein production of most of the tested cytokines was detected, together with a significant gene expression decrease in MMP9 and the up-regulation of MUC2 and TJP1. These results showed a fundamental capability of mEVs to modulate inflammation and their potential beneficial effect on the intestinal mucosa.